2020
DOI: 10.1101/2020.07.27.219568
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impairing flow-mediated endothelial remodeling reduces extravasation of tumor cells

Abstract: Tumor progression and metastatic dissemination are driven by cell-intrinsic and biomechanical cues that favor the growth of life-threatening secondary tumors. We recently identified prometastatic vascular regions with blood flow profiles that are permissive for the arrest of circulating tumor cells. We have further established that such flow profiles also control endothelial remodeling, which favors extravasation of arrested CTCs. Yet, how shear forces control endothelial remodeling is unknown. In the present … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…This cancer cell-derived exosomal paracrine pathway resulted in the upregulation of angiogenic pathways, with myofibroblasts acting as the intermediate player 49 . Strikingly, Follain and colleagues have highlighted that extravasation and endothelial remodelling is partly blood flow dependent and leads to increased metastases 50 , 51 . Their studies revealed that the vascular endothelium wall was actively remodelled around the extravasating circulating tumour cell (CTC), and hemodynamic cues from the sheer force of blood flow activated VEGFR pathways to encourage the exit of the cancer cell towards a metastatic site 51 .…”
Section: The Cancer Cell Secretome Activates the Tumour Microenvironmmentioning
confidence: 99%
See 1 more Smart Citation
“…This cancer cell-derived exosomal paracrine pathway resulted in the upregulation of angiogenic pathways, with myofibroblasts acting as the intermediate player 49 . Strikingly, Follain and colleagues have highlighted that extravasation and endothelial remodelling is partly blood flow dependent and leads to increased metastases 50 , 51 . Their studies revealed that the vascular endothelium wall was actively remodelled around the extravasating circulating tumour cell (CTC), and hemodynamic cues from the sheer force of blood flow activated VEGFR pathways to encourage the exit of the cancer cell towards a metastatic site 51 .…”
Section: The Cancer Cell Secretome Activates the Tumour Microenvironmmentioning
confidence: 99%
“…Strikingly, Follain and colleagues have highlighted that extravasation and endothelial remodelling is partly blood flow dependent and leads to increased metastases 50 , 51 . Their studies revealed that the vascular endothelium wall was actively remodelled around the extravasating circulating tumour cell (CTC), and hemodynamic cues from the sheer force of blood flow activated VEGFR pathways to encourage the exit of the cancer cell towards a metastatic site 51 . Thus, although this review focusses on the cancer secretome, the work by Follain et al .…”
Section: The Cancer Cell Secretome Activates the Tumour Microenvironmmentioning
confidence: 99%